MENINGKATKAN MINAT BELI KONSUMEN MELALUI STRATEGI SKIMMING PRICING DAN PENINGKATAN STORE IMAGE PADA PRODUK IPHONE - Amalia, Rizki (Awatara Publisher, 2024)
The iPhone experienced a decline in revenue, but the top brand index shows that the market share data for the iPhone in Indonesia experienced an increase in market share where in 2023 in the first phase the top brand index for the iPhone was at 12.40% and was ranked 3rd in the smartphone category below Samsung and Oppo. In the second phase, the iPhone market share rose by 24.70% and succeeded in occupying second place, replacing Oppo. The increase in market share shows that there is an increase in consumer buying interest in iPhone smartphone products in Indonesia. This research aims to test the influence of skimming pricing and store image variables on consumer buying interest in iPhone products. Using multiple regression analysis, 97 respondents were tested using a questionnaire instrument. The research results show that skimming pricing and store image have a positive influence on consumer buying interest in iPhone products